Letter (copy) : Assistance for Spain - Citrine, Walter, 1887-1983
030-0058-001 Secretary's WMC/HVT/CB. G.S. 17th September, 1938 Mr. D. Fernandez-Shaw, Spanish Embassy Commercial Office, 21, Cavendish Square, W, 1. Dear Mr. Fernandez-Shaw, Assistance for Spain. I have received your letter of the 5th instant, in which you ask me to put forward to the General Council a suggestion for a Winter Campaign to assist the victims of Fascist agression in Spain, and offering your co-operation. You will probably have seen from reports in the press that Congress has determined that a further effort shall be made to raise funds for the International Solidarity Fund. In connection with the last paragraph of your letter, I understand from Mr. Tewson that contact will be maintained with you. Yours sincerely, General Secretary. 292/946/30/58